Purification, Characterization, and Biocatalytic and Antibiofilm Activity of a Novel Dextranase from Talaromyces sp. - Mahasen Mohamed Ahmed Ebaya; Mohammed El-Mowafy; Mohamed Mohamed Adel El-Sokkary; Ramadan Hassan (International Journal of Microbiology)
Dextranase is a useful enzyme that catalyzes the degradation of dextran to low-molecular-weight fractions, which have many critical commercial and clinical applications. Endophytic fungi represent a source of both high heat-stable and pH-stable enzymes. In this study, from Delonix regia bark by plate assay, out of 12 isolated fungal strains, hyaline zones were detected in only one strain. By using the standard ITS rDNA sequencing analysis, the isolated strain was identified as Talaromyces sp. In the case of carbon source, in a medium containing 1% dextran T2000 as the sole carbon source, the maximum dextranase activity reached approximately 120 U/ml after incubation of 2 days where the optimum pH was 7.4. Peptone addition to the production medium as a sole nitrogen source was accompanied by a significant increase in the dextranase production. Similarly, some metal ions, such as Fe2+ and Zn2+, increased significantly enzyme production. However, there was no significant difference resulting from the addition of Cu2+. The crude dextranase was purified by ammonium sulfate fractionation, followed by Sephadex G100 chromatography with 28-fold purification. The produced dextranase was 45 kDa with an optimum activity at 37°C and a pH of 7. Moreover, the presence of MgSO4, FeSO4, and NH4SO4 increased the purified dextranase activity; however, SDS and EDTA decreased it. Interestingly, the produced dextranase expressed remarkable pH stability, temperature stability, and biofilm inhibition activity, reducing old-established biofilm by 86% and biofilm formation by 6%.